Bacterial Diversity and Community Composition in the Pyloric Ceca of Acanthaster solaris in the Xisha Islands - Yu Jiaoyang; Yu Xiaopeng; Yu Kefu; Ma Yuling (Redai dili)
Crown-of-Thorns Starfish (CoTS) are natural enemies of corals. Periodic outbreaks of CoTS and substantial feeding on corals lead to the degradation of coral reefs among the Indo-Pacific Ocean. Symbiotic bacteria play an important role in the development, reproduction, and digestion of CoTS. However, little is known about their composition and function. The pyloric ceca are the main digestive organ of CoTS. In this study, the composition and function of bacteria in the pyloric ceca of 15 adult A. solaris collected from the coral reef area of Xisha Islands were tested by high-throughput sequencing. A total of 833 bacterial OTUs were detected in the pyloric ceca, belonging to 26 phyla, 55 classes, 115 orders, 171 families, and 278 genera. The dominant phyla were Proteobacteria (94.50%), and the dominant genera were Vibrio (60.61%), Ralstonia (17.86%), and Photobacterium (6.64%). The symbiotic bacterial composition of other reef-associated organisms with different feeding habits, distributed in the Xisha Islands, were different. Composition of the pyloric cecal bacteria of CoTS were relatively similar to that of the coral symbiotic bacteria owing to the presence of some same bacteria genera in microbiome. Moreover, Vibrio was the dominant bacteria in both the pyloric cecal bacteria of CoTS and symbiotic bacteria of bleached Acropora solitaryensis, indicating high similarity. Therefore, the feeding habit of corals might be the important factor that affects the bacterial composition of the pyloric ceca of CoTS. The bacterial composition of the digestive tract of CoTS from the Great Barrier Reef of Australia and Japan showed the presence of Vibrionales, Burkholderiales, Rhizobiales, and Bacillales. However, significant regional differences were observed between the bacterial composition of the Xisha Island and Great Barrier Reef of Australia or Japan. Vibrio was more abundant in samples from the Xisha Islands than those from the Great Barrier Reef and Japan. This might be related to the massive coral bleaching events in the Xisha Islands from 2020 to 2021, which increased the relative abundance of Vibrio among the symbiotic bacteria of bleached corals. Additionally, as a potential Vibrio transmission vector, CoTS can pose a threat to the coral reef ecosystem in South China Sea. The results of bacterial function predict that their genome function was mainly focused on metabolism. The pathways with high relative abundance included carbohydrate, amino acid, cofactors and vitamins, and lipid metabolism. These results suggest that pyloric cecal bacteria may be involved in the daily physiological metabolic processes of CoTS. Thus, they might help digest corals by secreting hydrolytic enzymes. This study revealed the community composition, diversity, and affecting factors (feeding on coral) of pyloric cecal bacteria in CoTS from Xisha Islands, South China Sea.